DEVELOPING TRANSLATION STUDENTS’ PRAGMATIC COMPETENCE THROUGH CONTEXT-BASED ACTIVITIES IN ENGLISH-UZBEK LANGUAGE PAIRS (International conference on multidisciplinary science, 2025)
This article investigates how context-based activities can be effectively used to develop pragmatic competence among translation students working with English and Uzbek. The focus is on teaching learners to recognize and apply pragmatic elements such as speech acts, politeness strategies, and cultural context in translation tasks. The study draws on practical classroom experiences, translation samples, and student feedback to demonstrate how situational exercises improve both accuracy and naturalness in translated texts. By engaging with real-world communication scenarios, students learn to convey meaning beyond words, capturing tone, intention, and cultural appropriateness. The article concludes that incorporating context-based activities into translation training significantly enhances students’ communicative and intercultural skills, making them better equipped for professional translation tasks in both academic and applied settings.